(untitled) (Revista de Artes Marciales Asiáticas, 2019)
The 1st International Academic Taekwondo Conference Youngsan University was held on October 4, 2019 in Yangsan, Republic of Korea (ROK; i.e., South Korea). In an effort to bring together international researchers of taekwondo, three non-Korean presenters were invited and three accomplished academics, two non-Korean, made up the conference’s invited panelists. The topics presented were: 1) the shift in taekwondo’s peace promotion duties, 2) a discussion of mudo (“martial way” of life) in the Democratic People’s Republic of Korea (DPRK; i.e., North Korea), and 3) the decline of taekwondo as a combat sport. Although small in scale, the conference built upon previous taekwondo academic endeavors in- and outside of Korea. Most importantly, the conference highlighted the fact that non-Korean academics are furthering the research field beyond the nationalistic concepts still held in the Korean taekwondo community. The event immediately garnered interest in an expanded conference for 2020.